Improvement Students’ Spatial Ability and Self Confidence Through Inquiry Learning With Geogebra at SMA Negeri 19 Medan - Malau, Tuti Mariani (Kreano, Jurnal Matematika Kreatif-Inovatif, 2017)
This study aims to find out the difference of spatial ability and self confidence students improvement who were taught through inquiry learning model with GeoGebra (ILMG) and inquiry learning model without GeoGebra (ILMWG). The population of the study was the students at SMAN 19 Medan. The sample was the tenth grade students who randomly selected. Experimental 1 class were taught by ILMG and experimental 2 class were taught by ILMWG. The instruments of this study were spatial ability test and self confidence scale. The data were analyzed with the analysis of variance and Mann-Whitney analysis. In general, The results of the study shows that the improvement of students’ spatial ability and self confidence who were taught through ILMG higher than ILMWG.Penelitian ini bertujuan untuk melihat perbedaan peningkatan kemampuan keruangan dan percaya diri siswa yang diajar dengan model pembelajaran inkuiri berbantuan GeoGebra (MPIG) dan model pembelajaran inkuiri tanpa berbantuan GeoGebra (MPITG). Populasi dari penelitian ini adalah siswa-siswi SMA Negeri 19 Medan. Sampelnya adalah siswa kelas X yang dipilih secara acak. Kelas eksperimen 1 diajar dengan menggunakan MPIG dan kelas eksperimen 2 diajar dengan menggunakan MPITG. Instrumen penelitian ini adalah tes kemampuan keruangan dan skala percaya diri. Data dianalisis dengan menggunakan analisis kovarian dan uji Mann-Whitney. Hasil penelitian secara umum menunjukkan bahwa peningkatan kemampuan keruangan dan percaya diri siswa yang diajar melalui MPIG lebih tinggi daripada melalui MPITG.